2021
DOI: 10.1016/j.sdentj.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Lithium di silicate ceramic surface treated with Er,Cr:YSGG and other conditioning regimes bonded to orthodontic bracket

Abstract: Aim To assess bond integrity and modes of failure of metallic brackets to lithium disilicate ceramics (LDC) conditioned with Er,Cr:YSGG laser (ECL). Material and methods Sixty LDC were arbitrarily allocated into six groups (n = 15) according to the type of ceramic surface conditioning treatment. Group 1 surface treated with silane (S) only, group 2 surface etched with hydrofluoric acid (HF)+ S, group 3 surface conditioned with HF+ ultrasonic bath (UB)+ S, group 4 sand b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Sundfeld et al and Garboza et al showed that etching lithium disilicate ceramics with 10% HFA for 20 s with subsequent silane application resulted in high bond strengths [20,21]. Moreover, Al Rifaiy in 2018 [22] and Alqerban in 2019 [23] found that the highest shear bond strength (SBS) was obtained by increasing the etching time of 9.5% HFA to 90 s and 60 s, respectively. In 2020, Souza et al compared different HFA etching times (20, 60 and 120 s + silanization or Scotch Bond Universal) on the bond strength of lithium disilicate.…”
Section: Manufacturing Technologies Allow It To Have Both High Perfor...mentioning
confidence: 99%
“…Sundfeld et al and Garboza et al showed that etching lithium disilicate ceramics with 10% HFA for 20 s with subsequent silane application resulted in high bond strengths [20,21]. Moreover, Al Rifaiy in 2018 [22] and Alqerban in 2019 [23] found that the highest shear bond strength (SBS) was obtained by increasing the etching time of 9.5% HFA to 90 s and 60 s, respectively. In 2020, Souza et al compared different HFA etching times (20, 60 and 120 s + silanization or Scotch Bond Universal) on the bond strength of lithium disilicate.…”
Section: Manufacturing Technologies Allow It To Have Both High Perfor...mentioning
confidence: 99%
“…However, a large number of studies showed that AA using 30 μm aluminium oxide with silane coupling and tribochemical coating (CoJet-Sand, 3M ESPE, Seefeld, Germany) produced very strong bonds for brackets to ceramic surfaces [54,76,77,79,80,84]. [85][86][87][88]. It is a one-step conditioning agent that combines ammonium polyfluoride to etch ceramic surfaces along with silane.…”
Section: International Journal Of Dentistrymentioning
confidence: 99%
“…It is a one-step conditioning agent that combines ammonium polyfluoride to etch ceramic surfaces along with silane. It was found to achieve bond strengths that are lower than conventional etching with HF and silane, but still clinically acceptable [85][86][87][88]. Even though it is a perfectly feasible option for prosthodontic use, it is highly questionable whether it should be used for orthodontic bonding of brackets, since it has been contraindicated for intraoral use by the manufacturer due to its toxicity.…”
Section: International Journal Of Dentistrymentioning
confidence: 99%
“…In this study, an examination of the effect of laser surface irradiation on ceramic samples was done by SEM and a profilometer. Also, Er,Cr:YSGG irradiated samples with power 5 W,25 Hz have a uniform smooth surface topography opposite to the acid-etched samples; this disagrees with (Alqerban et al, 2021), who speculated that comparable bond strength treated by Er,Cr:YSGG at 4.5 W, 30 Hz (17.09 ± 1.114, P > 0.05) to HF (17.85 ± 1.25, P>0.05) is due to the formation of micro-depths and abrasion on the LDC surface.…”
Section: Discussionmentioning
confidence: 80%